Poly-lactic Acid/Gelatin Nanofiber (PLA/GTNF) Conduits Containing Platelet-Rich Plasma for Peripheral Nerve Regeneration - Farzamfar1, Saeed; Esmailpour1, Farshid; Rahmati2, Majid; Vaez3, Ahmad; Mirzaii4, Mehdi; Garmabi2, Behzad; Shayannia2, Asghar; Ebrahimi5, Elham; Vahedi6*, Hamid; Salehi7**, Majid (Shahroud Journal of Medical Sciences, 2017)
Background: Polymeric scaffolds have achieved immense importance in the field of nerve tissue engineering.Methods: In the present study, the combination of thermally induced phase separation (TIPS) and electrospinning methods were used to fabricate poly- (lactic acid)/gelatin nanofiber/PRP-scaffolds. Several physical and mechanical tests (weight loss measurement, surface wettability, porosity, microstructure observation via SEM photography, mechanical tests such as tensile strength, and Young modulus) and cellular assays (MTT assay and DAPI staining) were explored to assess the scaffolds capability to serve as neural guidance conduit. In this study, we hypothesized that conduits enriched with PRP may provide a better regenerative environment for nerve tissue repair. Results: This study suggests that GTNF/PRP incorporated scaffolds revealed better biological and physical properties than PLA only scaffolds.Conclusions: Results indicate that when GTNF/PRP is incorporated into the PLA scaffolds, resultant mechanical properties, porosity and cell attachment, and viability in vitro were better than pure PLA.